Evaluation of the antimicrobial, antioxidant and cytoprotective activity of kercetin against the toxic action of barium chloride (Research, Society and Development, 2021)
This study aimed to evaluate the antimicrobial, antioxidant and cytoprotective activity of quercetin against the toxicity of barium chloride. The test solution was prepared from the dilution using DMSO, later dilutions were made in order to obtain different concentrations. The Minimum Inhibitory Concentration (MIC) was obtained through microdilutions in broth, for reading the tests with the bacteria a solution of sodium resazurin was added in each well (20 µL) and the plates were left to stand for 1 h at room temperature. To evaluate the cytoprotective effect of quercetin to barium chloride, eppendorfs were prepared containing subinhibitory concentration of the sample and suspensions of 105 CFU / ml of Escherichia coli 06 (EC 06) and Candida albicans (CA 40006) in TRIS M9 medium. The solution was distributed on the microdilution plate. Then 100 µL of barium chloride was added to the first well, followed by successive microdilutions until the penultimate well. The antioxidant action of the substance was evaluated using the DPPH method (1,1-diphenyl-2-picryl-hydrazyl), the tests were carried out in triplicate, noting that quercetin is effective in its antioxidant action. Quercetin had no action on MIC, with a result of ≥ 1024 µg / ml. He observed that quercetin had a cytoprotective effect against Escherichia coli, when associated with barium chloride, quercetin showed positive results related to the action of its cytoprotective activity. These results open possibilities for the evolution of complementary studies and the use in contaminated environments.